Scaffold mediated regulation of MAPK signaling and cytoskeletal dynamics: A perspective - Pullikuth, Ashok K. (2007)
Cell migration is critical for many physiological processes and is often misregulated in developmental disorders and pathological conditions including cancer and neurodegeneration. MAPK signaling and the Rho family of proteins are known regulators of cell migration that exert their influence on cellular cytoskeleton during cell adhesion and migration. Here we review data supporting the view that localized ERK signaling mediated through recently identified scaffold proteins may regulate cell migration.